ANALISIS REABILITAS INSTRUMEN ASESMEN PADA KETERAMPILAN BERPIKIR KRITIS DALAM PEMBELAJARAN PAI DI SDN KOROULON 1 - Titis Wahyu Muji Lestari; Shofia Maulida; Suwadi (LPPM STAI Muhammadiyah Probolinggo, 2025)
Islamic Religious Education (PAI) plays an important role in shaping the character, morals, and spirituality of students, as well as instilling critical thinking skills that are much needed in the era of globalization and digitalization. However, measuring critical thinking skills in PAI learning still faces challenges, especially related to the reliability of the assessment instruments used. This study aims to analyze the reliability of the critical thinking skills assessment instrument in PAI learning in class V of SDN Koroulon 1. The results of the analysis show that the assessment instrument has a good reliability value, with a Cronbach Alpha coefficient ≥ 0.7, so it can be relied on to measure students' critical thinking skills consistently. This finding emphasizes the importance of using reliable instruments in evaluating PAI learning to ensure the achievement of 21st century learning goals, namely forming students who are critical, reflective, and have Islamic character. This study recommends the development of more valid and relevant assessment instruments and the use of instruments that have been tested for reliability by teachers and researchers in PAI learning.